Diffuse Ionized Gas in the Anticenter of the Milky Way - Shiming Wen; Wei Zhang; Lin Ma; Yunning Zhao; Man I. Lam; Chaojian Wu; Juanjuan Ren; Jianjun Chen; Yuzhong Wu; Guozhen Hu; Yonghui Hou; Yongheng Zhao; et al. (The Astronomical Journal)
Using data from the Large Area Multi-Object fiber Spectroscopic Telescope Medium-Resolution Spectroscopic Survey of Nebulae, we create a sample of 17,821 diffuse ionized gas spectra in the anticenter region of the Milky Way by excluding fibers in the directions of H ii regions and supernova remnants. We then analyze the radial and vertical distributions of three line ratios ([N ii ]/H α , [S ii ]/H α , and [S ii ]/[N ii ]), as well as the oxygen abundance. [N ii ]/H α and [S ii ]/H α do not exhibit a consistent, monotonic decrease with increasing Galactocentric distance ( R _gal ). Instead, they show enhancement within the interarm region, positioned between the Local Arm and the Perseus Arm. [S ii ]/[N ii ] has a radial gradient of 0.1415 ± 0.0646 kpc ^−1 for the inner disk (8.34 <  R _gal  < 9.65 kpc) and remains nearly flat for the outer disk ( R _gal  > 9.65 kpc). In the vertical direction, [N ii ]/H α , [S ii ]/H α , and [S ii ]/[N ii ] increase with increasing Galactic disk height (∣ z ∣) in both southern and northern disks. Based on the N2S2H α method, which combines [S ii ]/[N ii ] and [N ii ]/H α , we estimate the oxygen abundance. The oxygen abundance exhibits a consistent radial gradient with R _gal , featuring a slope of −0.0559 ± 0.0209 dex kpc ^−1 for the inner disk and a similar slope of −0.0429 ± 0.0599 dex kpc ^−1 for the outer disk. A single linear fitting to the entire disk yields a slope of −0.0317 ± 0.0124 dex kpc ^−1 . In the vertical direction, the oxygen abundance decreases with increasing ∣ z ∣ in both southern and northern disks.